ANSI/ IEEE C37.5-1979 : IEEE Guide for Calculation of Fault Currents for Application of AC High-Voltage Circuit Breakers Rated on a Total Current Basis (IEEE, 1979)
This standard is a guide for the calculation of fault currents for the application of AC high-voltage circuit breakers rated on a total current basis. This guide is intended for general use in the application of circuit breakers. Familiarity with other American National Standards applying to circuit breakers is assumed, and provisions of these standards are indicated herein only when necessary for clarity in describing application requirements.
Keywords: High voltages.; Electric power distribution.